Accuracy of toric intraocular lens power calculation depending on different keratometry values using a novel network based software platform - Ramsauer, Michaela; Luft, Nikolaus; Vounotrypidis, Efstathios; Priglinger, Siegfried G.; Mayer, Wolfgang J. (Frontiers in Medicine, 2024)
Purpose: To compare different corneal keratometry readings (swept-source-OCT-assisted biometry and Scheimpflug imaging) with a novel software platform for calculation of toric intraocular lenses. Setting: Department of Ophthalmology, Ludwig-Maximilians-University, Munich, Germany. Design: Retrospective, non-randomized, clinical trial. Methods: Twenty-three eyes undergoing toric intraocular lens implantation were included. Inclusion criteria were preoperative regular corneal astigmatism of at least 1.00D, no previous refractive surgery, no ocular surface diseases and no maculopathies. Lens exchange was performed with CALLISTO eye (Zeiss). For each patient, the expected postoperative residual refraction was calculated depending on three different corneal parameters of two different devices: standard K-front (K) and total keratometry (TK) obtained by a swept-source-OCT-assisted biometry system (IOL Master 700, Zeiss) as well as total corneal refractive power (TCRP) obtained by a Scheimpflug device (Pentacam AXL, Oculus). Barrett's formula for toric intraocular lenses was used for all calculations within a novel software platform (EQ workplace, Zeiss FORUM®). Results were statistically compared with postoperative refraction calculated according to the Harris dioptric power matrix. Results: The standard K values (mean PE 0.02D±0.45D) and TK values (mean PE 0.09D±0.43D) of the IOL Master 700 reached similar results (p=0.96). 78% of eyes in both K and TK groups achieved SE within ± 0.5 D of attempted correction and all eyes (100%) were within ±1.0 D of attempted correction in both groups. By contrast, the prediction error in the IOL calculation using the TCRP of the Scheimpflug device was significantly greater (mean PE -0,56D±0.49D; p=0.00 vs. standard K and p=0.00 vs. TK) with adjusted refractive indices. 39% and 91% of eyes in the TCRP group achieved SE within ± 0.5 D (p=0.008 K v. TCRP and p=0.005 TK v. TCRP) and ±1.0 D (p=0.14 v. TCRP) of attempted correction, respectively. Conclusions: All three corneal parameters (standard K, TK, TCRP) performed well in calculating toric IOLs. The most accurate refractive outcomes in toric IOL implantation were achieved by IOL calculations based on Swept-source-OCT-assisted biometry. The SS-OCT-based K-front and TK values achieve comparable results in the calculation of toric IOLs.